A within-person perspective on feedback seeking about task performance - ANSEEL, Frederik (Institutional Knowledge at Singapore Management University, 2006)
In organisations, feedback about multiple performance dimensions is often available. Consequently, employees have to decide on which performance dimensions they will be seeking feedback. In a lab experiment 126 students indicated on which performance dimensions they wanted to receive feedback after completing a computerized in-basket task. Results showed that participants especially sought feedback about their best and most important performance dimensions. Individuals with a high learning goal orientation sought more feedback about their least important performance dimensions as compared to individuals with a low learning goal orientation. In general, results indicated that previous findings obtained in between-person studies of feedback seeking hold relatively well at a within-person level of analysis. The results of the current study illustrate how adopting a within-person perspective can broaden our understanding of the feedback-seeking process in organisations.